2021
DOI: 10.1002/zoo.21653
|View full text |Cite
|
Sign up to set email alerts
|

Colony composition and nutrient analysis of Polyrhachis dives ants, a natural prey of the Chinese pangolin (Manis pentadactyla)

Abstract: The Chinese pangolin (Manis pentadactyla) is a critically endangered mammal with a highly specialized diet. To enhance nutritional knowledge of its diet, we analyzed the colony composition of a nest of Polyrhachis dives ants, which is the key natural prey in the Chinese pangolin's diet. In addition, we determined the nutrient composition of the total colony compared with adult ants. Nutrients quantified in this study included: crude protein, crude fat, carbohydrate, and amino acids, minerals, and vitamins, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Currently, there are fewer studies related to tumors in Chinese pangolin. Stomach tumors of the pangolin were reported in 1984 and 1986 [ 13 , 14 ], but the site of the tumour was later confirmed to be pyloric pillow of the stomach [ 15 ]. The National Forestry and Grassland Administration pangolin conservation research center is responsible for the artificial rescue of Chinese pangolin throughout the country.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are fewer studies related to tumors in Chinese pangolin. Stomach tumors of the pangolin were reported in 1984 and 1986 [ 13 , 14 ], but the site of the tumour was later confirmed to be pyloric pillow of the stomach [ 15 ]. The National Forestry and Grassland Administration pangolin conservation research center is responsible for the artificial rescue of Chinese pangolin throughout the country.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that their weight doubled after 15 months of continuous feeding with Manis pentadactyla , indicating that their metabolism is slow, and overfeeding should be avoided to reduce excessive growth or adult obesity [ 39 ]. Important in evaluating digestibility is the fact that the main items in the natural diet (ants and termites) have exoskeletons with high levels of chitin [ 46 , 50 ]. Chitin is the most abundant biopolymer in nature after cellulose.…”
Section: Other Factors Affecting the Nutrition Of Pangolinsmentioning
confidence: 99%
“… Vitamin concentrations in natural food and formula under human care of pangolins [ 46 , 47 , 48 , 49 ]. Notes: Formula 2 includes cat food, ant powder, yellow mealworms, eggs, apples, water, amino acid, astragalus, and trace elements; formula 4 includes cat food, ant powder, yellow mealworms, eggs, apples, carrots, cicada pupas, water, and amino acid.…”
Section: Figurementioning
confidence: 99%